Psychological characteristics of self-realization of students with disabilities - Olga Kuprieieva (Social Welfare: Interdisciplinary Approach)
The article presents the results of the study aimed at identifying of psychological characteristics of self-realization of students with disabilities. It was found that self-realization successfulness for the studied students with disabilities is determined by their desire for self-development and expansion of their potential; existence of positive integral self-attitude that determines their internal activities; availability and awareness of self-actualization values, life goals, emotional richness and comprehensive interpretation of their life processes; balanced time perspectives